The Impact of Gender-Based Segregation Class Towards Students' Speaking Competences - Inayah, Lestiyani (Edulingua: Jurnal Linguistiks Terapan dan Pendidikan Bahasa Inggris, 2023)
This research aimed to find out the impact of gender-based segregation class towards students’ speaking competences. This research is intended in SMA Islam Sultan Agung 1 Semarang which is Islamic-based schools involving 20 students who are 10 male students and 10 female students. This is a descriptive qualitative study which utilizes Independent Sample T-Test as the tool of analyzing the data. The data is conducted in the middle of English learning in the classroom. This research iis conducted because there are a few schools which implement the gender-based segregation class in their school. SMA Islam Sultan Agung 1 Semarang is the first school to implement the gender-based segregation class. It is also a new and unique phenomenon for researchers who take the role of preservice teacher in the school. The result of this research shows that there is a significant difference between male and female students in their speaking competence, especially in their own classroom.